Nomadland : surviving America in the twenty-first century - Bruder, Jessica (W. W. Norton & Company, 2017)
From the beet fields of North Dakota to the National Forest campgrounds of California to Amazon's CamperForce program in Texas, employers have discovered a new, low-cost labor pool, made up largely of transient older Americans. Finding that social security comes up short, often underwater on mortgages, these invisible casualties of the Great Recession have taken to the road by the tens of thousands in late-model RVs, travel trailers, and vans, forming a growing community of nomads: migrant laborers who call themselves "workampers." In a secondhand vehicle she christens "Van Halen," Jessica Bruder hits the road to get to know her subjects more intimately. Accompanying her irrepressible protagonist, Linda May, and others, from campground toilet cleaning to warehouse product scanning to desert reunions, then moving on to the dangerous work of beet harvesting, Bruder tells an eye-opening tale of the dark underbelly of the American economy -- foreshadowing the precarious future that awaits many more of us. At the same time, she celebrates the exceptional resilience and creativity of these quintessential Americans who have given up ordinary rootedness to survive. Like Linda May, who dreams of finding land on which to build her own sustainable "Earthship" home, they have not given up hope.